Parenchymal lung abnormalities following hospitalisation for COVID-19 and viral pneumonitis: a systematic review and meta-analysis. Issue 2 (25th March 2022) - Fabbri, Laura; Moss, Samuel; Khan, Fasihul A; Chi, Wenjie; Xia, Jun; Robinson, Karen; Smyth, Alan Robert; Jenkins, Gisli; Stewart, Iain
Abstract : Introduction: Persisting respiratory symptoms in COVID-19 survivors may be related to development of pulmonary fibrosis. We assessed the proportion of chest CT scans and pulmonary function tests consistent with parenchymal lung disease in the follow-up of people hospitalised with COVID-19 and viral pneumonitis. Methods: Systematic review and random effects meta-analysis of proportions using studies of adults hospitalised with SARS-CoV-2, SARS-CoV, MERS-CoV or influenza pneumonia and followed up within 12 months. Searches performed in MEDLINE and Embase. Primary outcomes were proportion of radiological sequelae on CT scans; restrictive impairment; impaired gas transfer. Heterogeneity was explored in meta-regression. Results: Ninety-five studies (98.9% observational) were included in qualitative synthesis, 70 were suitable for meta-analysis including 60 SARS-CoV-2 studies with a median follow-up of 3 months. In SARS-CoV-2, the overall estimated proportion of inflammatory sequelae was 50% during follow-up (0.50; 95% CI 0.41 to 0.58; I 2 =95%), fibrotic sequelae were estimated in 29% (0.29; 95% CI 0.22 to 0.37; I 2 =94.1%). Follow-up time was significantly associated with estimates of inflammatory sequelae (−0.036; 95% CI −0.068 to –0.004; p=0.029), associations with fibrotic sequelae did not reach significance (−0.021; 95% CI −0.051 to 0.009; p=0.176). Impaired gas transfer was estimated at 38% of lung function tests (0.38 95% CI 0.32 to 0.44; I 2 =92.1%), which was greater than restrictive impairment (0.17; 95% CI 0.13 to 0.23; I 2 =92.5%), neither were associated with follow-up time (p=0.207; p=0.864). Discussion: Sequelae consistent with parenchymal lung disease were observed following COVID-19 and other viral pneumonitis. Estimates should be interpreted with caution due to high heterogeneity, differences in study casemix and initial severity. PROSPERO registration number: CRD42020183139.